An Improved Sporulation Method for Producing Asexual Zoospores of Pythium aphanidermatum on Culture Medium - Yu Jin Kim; Seung Hyo Baek; Elena Volynchikova; Mee Kyung Sang; Ki Deok Kim (Mycobiology, 2025)
An improved sporulation method for Pythium aphanidermatum on 10% V8-juice agar was developed to generate substantial quantities of zoospores. We conducted experiments using a 4 × 4 factorial design to evaluate the effects of temperature (20, 25, 30, and 35 °C) and incubation time (2, 3, 4, and 5 days) on zoospore production from isolates HSv05 and KACC 48066. The results indicated that a temperature of 30 °C consistently yielded the highest numbers of zoospores across all incubation periods. Applying the same temperature (30 °C) and all incubation periods to other isolates (CCp03, CCp04, CCp05, HSv10, and KACC 40156) also resulted in higher numbers of zoospores regardless of incubation times compared with that under the control condition (25 °C and 2 days). Further virulence tests of isolate HSv05 revealed that high concentrations of zoospores (5 × 102 − 105 zoospores/ml) induced severe rot symptoms; however, a low concentration of 102 zoospores/ml produced only considerably weak symptoms on inoculated potato tubers. No symptoms appeared in tubers inoculated with 0 (uninoculated control) or 101 zoospores/ml. These findings suggest that our sporulation method can help obtain adequate zoospores for various basic and applied studies, including pathogen identification, virulence assessment, resistance resource screening, and control strategy development.